Pengaruh Good Corporate Governance Terhadap Profitabilitas dengan Kinerja Keuangan Sebagai Variabel Moderasi - Hajering, Hajering; Nur Wahyuni; Zulkahfi, Zulkahfi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to determine the effect of the Good Corporate Governance (GCG) system on profitability with financial performance as a moderating variable in Sri-Kehati index companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sample was determined by saturated sample technique. The samples in this study were 35 companies. This research is quantitative research. The data used is secondary data, namely company financial report data obtained from the annual report of each company website. Data analysis techniques using SmartPLS 4.0 software. The results showed that: Good Corporate Governance variables represented by institutional ownership and independent commissioners have a positive and significant effect on company profitability. And the financial performance variables projected through DER and TATO strengthen the influence of Good Corporate Governance on company profitability. This means that the better GCG is moderated by the ratio of activity and solvency, the company's profitability will increase.